Landfill site selection using GIS and Multicriteria Decision Analysis : A Case Study of Butwal Sub- Metropolitan City - Banstola, Prabin; Bhusal, Keshav Raj; Adhikari, Surya (Journal of Advanced Research in Geo Sciences & Remote Sensing; Vol 10 No 1&2 (2023): Journal of Advanced Research in Geo Sciences & Remote Sensing, 2024)
In developing country like Nepal there are not enough technology for scientific solid waste management and is dependent on traditional direct wastes disposal on specified area (landfill site). This study utilizes GIS and Multicriteria Decision Analysis for the selection of landfill sites in one of the growing city of Nepal, Butwal. Different factors like road, river, slope, land use land cover(LULC) and built-up were determined according to past literatures and existing data availability. The data used in this study are open data available through openstreetmap and QGIS software was used for data cleaning and analysis. The LULC data used was downloaded from Esri 10 m high resolution data 2022 from Esri living atlas. Each data were differentiated into five classes unsuitable, less suitable, moderately suitable, suitable and highly suitable on basis of proximity and their characteristics. Weightage was given to each criteria on basis of Analytical Hierarchy Process (AHP) through pairwise comparison matrix. Finally, overlay resulting a final landfill suitability was obtained. The result shows 0.01% highly suitable, 10.61% suitable, 53.12% moderately suitable, 34.96% less suitable and 1.29% unsuitable land availability for landfill site in Butwal. It is seen that there is very less highly suitable region for landfill site in Butwal and suitable region for landfill lies in southern part of Semlar and Motipur with neighbouring region of Sudhdhodhan Gaupalika, northern part of Belbas, eastern part close to Charange and few in Northern region. Thus, obtained result is supposed to help in the decision making for proper landfill site selection.